Ժամանակակից հայերենի ժամանականիշ բառերի ծագումնաբանությունը - Ռեբեկա Մարգարյան (ՀՀ ԳԱԱ հրատ.)
Армянский язык имеет богатый словарный запас. Часть этого словарного запаса составляют также времяуказательные слова, которые по происхождению делятся на три группы: исконно армянские слова, полученные или унаследованные и заимствованные. The Armenian language has a rich vocabulary. Tense-marking words form part of its vocabulary. According to the etymology, these markers are of three types: native Armenian words, received or inherited words and borrowings.
Keywords: Philology; Linguistics; Language and Literature